2012
DOI: 10.1002/ajim.22057
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus infection and waste collection: Prevalence, risk factors, and infection pathway

Abstract: Occupational exposure to waste is a possible risk factor for HBV infection. Occupational injury with sharp instruments could be a means of hepatitis B virus transmission. Immunization of MSWWs and adoption of more safe ways for waste collection could be considered in order to control the risk of HBV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
59
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 13 publications
(28 reference statements)
3
59
1
1
Order By: Relevance
“…Occupational exposure to waste is a possible risk factor for HBV infection, and injury with needle sticks/sharp instruments could be associated with this infection 13 . A high prevalence of HBV infection (34.4%) was found among recyclable waste resULTs Between April 2010 and May 2011, recyclable waste pickers were recruited from all recycling cooperatives, and all individuals were invited to participate in this study.…”
mentioning
confidence: 99%
“…Occupational exposure to waste is a possible risk factor for HBV infection, and injury with needle sticks/sharp instruments could be associated with this infection 13 . A high prevalence of HBV infection (34.4%) was found among recyclable waste resULTs Between April 2010 and May 2011, recyclable waste pickers were recruited from all recycling cooperatives, and all individuals were invited to participate in this study.…”
mentioning
confidence: 99%
“…These studies show the vulnerability of the workers who are exposed to infection without the appropriate immunization 5,21,22,26,29 .…”
Section: Discussionmentioning
confidence: 94%
“…Six of the studies concluded that workers collecting urban solid waste are exposed to greater risk when compared with those who have no exposure 19,21,22,23,24,25 , although one study found no such additional risk 5 . With regard to health care waste, three studies indicate higher risk among those collecting than those working with urban solid waste 26,27,28 , and a fourth study found none 29 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…En otros estudios se buscó asociación entre el trabajo y las enfermedades infecciosas (hepatitis A Hepatitis B, Toxoplasmosis, Leptospirosis) (7) relacionándolos con aerosoles infecciosos (8,9). Otras publicaciones encontraron datos de exposición a riesgos biológicos, químicos, físicos, ergonómicos, aspectos psicosociales (10); en otras se buscaron condiciones de salud, afecciones respiratorias y ergonómicas (11)(12)(13).…”
Section: Introductionunclassified